South African physiotherapists' attitudes to medicine prescription as an extension of practice - Tsungirirai V. Kakono; Desmond Mathye; Sarel J. Brand; Werner Cordier (AOSIS, 2023)
Background: The extension of medicine prescription rights to other healthcare providers was proposed to reduce pharmacotherapeutic service delivery challenges in the South African healthcare sector. The scope of practice of physiotherapists is being reviewed to possibly include prescription rights to promote service delivery. Objectives: Our study assessed the attitudes of registered South African physiotherapists to the inclusion of prescription rights in their scope of practice, including enablers and challenges, and the drug classes they believe to be most relevant. Method: A cross-sectional descriptive survey of South African registered physiotherapists was completed using an online questionnaire. Results: A total of 359 participants completed the questionnaire, where 88.2% agreed that prescribing rights should be introduced, and 87.64% would want to be trained to prescribe. Participants identified several benefits: improved service delivery (91.3%); reduced healthcare delivery costs (89.8%); decreased need for multiple healthcare practitioner consultations (93.2%). Concerns included: inadequate training (55%); increased workload (18.7%); increased insurance premiums against medical liability claims (46.2%). Drugs of relevance included analgesics (95.6%) and bronchodilators (96.0%), while low preference was placed on drugs unrelated to physiotherapy. Chi-square analysis revealed associations between specific drug classes and fields of expertise. Conclusion: South African physiotherapists agree that prescribing and a limited formulary would benefit their scope of practice; however, educational concerns are evident. Clinical implications: Findings support the drive to extend the South African physiotherapy scope of practice, however, investigation will be needed to determine the most appropriate way to capacitate future physiotherapists and current graduates should the extension be approved.